2017
DOI: 10.1186/s12936-017-1990-x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs in malaria infection: bench to bedside

Abstract: Severe malaria has a poor prognosis with a morbidity rate of 80% in tropical areas. The early parasite detection is one of the effective means to prevent severe malaria of which specific treatment strategies are limited. Many clinical characteristics and laboratory testings have been used for the early diagnosis and prediction of severe disease. However, a few of these factors could be applied to clinical practice. MicroRNAs (miRNAs) were demonstrated as useful biomarkers in many diseases such as malignant dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 79 publications
0
29
1
Order By: Relevance
“…Another study conducted on controlled human blood-stage infection (CHMI) has shown the dichotomous miRNA expression distinguishing high-miR responders from low-miR responders with significantly enhanced antimalarial antibody responses in the high-miR responders group [ 47 ]. At present there is no approved diagnostic modality available to detect the severity of the P. vivax malaria [ 48 ]. In the present study we identified the potential whole blood miRNA marker for the probable diagnosis of complicated P. vivax malaria using miRNA microarray.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study conducted on controlled human blood-stage infection (CHMI) has shown the dichotomous miRNA expression distinguishing high-miR responders from low-miR responders with significantly enhanced antimalarial antibody responses in the high-miR responders group [ 47 ]. At present there is no approved diagnostic modality available to detect the severity of the P. vivax malaria [ 48 ]. In the present study we identified the potential whole blood miRNA marker for the probable diagnosis of complicated P. vivax malaria using miRNA microarray.…”
Section: Discussionmentioning
confidence: 99%
“…However, microscopy is routinely being used for the diagnosis of malaria and remains the gold standard. Also rapid antigen detection test (RDT) and molecular tests (PCR and LAMP) have also been used for the diagnosis of malaria [ 13 ]. But we do not have any technique that can be used in order to differentiate the complicated P. vivax malaria from the uncomplicated P. vivax malaria.…”
Section: Introductionmentioning
confidence: 99%
“…Those findings provide the first evidence of the protective role from a specific miRNA in human malaria. Recently, it was shown that circulating levels of miR-451 and miR-16 were downregulated in patients infected with Plasmodium vivax at parasitic stages or with multi-organ failure involvement ( 25 , 52 ). This association of miRNAs profile with clinical severity of malaria infection emphasize that miRNAs are potential tools for diagnosis and therapeutics for parasitic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The downregulated expression of miRNA‐451 and miRNA‐16 was due to the destruction of the RBCs containing miRNA by the parasite and hypersplenism that is destruction of the RBCs by spleen (LaMonte et al, ). MiRNA‐92 and miRNA‐17 were responsible for renal failure regulating the TGF‐β signaling, inducing apoptosis in the renal progenitor cells (Chamnanchanunt, Fucharoen, & Umemura, ). MiRNA‐92 and miRNA‐17 were responsible for renal failure regulating the TGF‐β signaling, inducing apoptosis in the renal progenitor cells (Chamnanchanunt et al, ).…”
Section: Role Of Circulatory Mirna For the Diagnosis Of Human Infectimentioning
confidence: 99%